DETERMINANTS OF FARMERS' PERCEPTION AND ADAPTATION STRATEGIES TO CLIMATE CHANGE IN IWO LOCAL GOVERNMENT AREA OF OSUN STATE, NIGERIA. - Akintobi, Olarenwaju S. (FUDMA JOURNAL OF SCIENCES, 2023)
This study was carried out to identify the adaptation measures employed by the farmers and the determination of the pattern of crop production as a result of perceived effect of climate change. Both simple and multi stage random sampling were used to select 120 respondents from the 15 wards making up the local government. Pearson Product Moment Correlation was used to determine the relationship between the variables. The study revealed most of the respondents were relatively older between ages of 50-59, 76.7% were married, and 36.6% of the entire population possess primary education, It is evident that farmers in the study area are well informed of the changes in climatic variables in their environment and are employing adaptation measures which include crop rotation, tillage methods and livelihood diversification to curb the negative effect of climate change. However, multiple farming, multiple cropping and ley farming are the crop production patterns used by the farmers as a result of perceived effect of climate change. Years of schooling and Farming experience showed a significant relationship with the farmers’ climate change perception. Conclusively, policies must aim at promoting farm level adaptation; timely advice and help from research institution and training workshop for arable farmers, use of interpersonal and mass media for farmers awareness and timely and accessible meteorological reports on fluctuating climatic variables
Keywords: Climate Change, Perception, Adaption, Climatic Variables, Crop production